MIDDLE EOCENE TO EARLY MIOCENE FORAMINIFERAL BIOSTRATIGRAPHY IN THE EPILIGURIAN SUCCESSION (NORTHERN APENNINES, ITALY) - NICOLETTA MANCIN; CAMILLA PIRINI (Rivista Italiana di Paleontologia e Stratigrafia, 2001)
A quantitative biostratigraphical study was performed on the foraminiferal assemblages from 15 stratigraphic sections of the Epiligurian Succession (Middle Eocene-Early Miocene, Northern Apennines, Italy). This study enabled us to identify the presence of some of the standard bioevents and to note that other bioevents are absent or show a different chronostratigraphic range. Other additional bioevents, identified throughout the area, have therefore been utilised to improve the biostratigraphical resolution of the Epiligurian sediments. These bioevents include the massive extinction of the muricate species at the Bartonian/Priabonian boundary; the increasing abundance of Paragloborotalia opima opima near Subzone P21a/P21b and the Rupelian/Chattian boundaries; and the FO of Globoquadrina dehiscens at the Subzone N4a/N4b boundary.